Sulfide solid electrolyte, method for producing sulfide solid electrolyte, electrode body and all-solid-state battery
By using a solid sulfide electrolyte containing Li, P and S in the electrode body of the lithium battery and adding tetrahydrofuran during its synthesis, the problem of low ion transport efficiency in existing batteries is solved, and the battery performance is improved.
Patent Information
- Application Number
- CN202010234109.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-11
- Filing Date
- 2020-03-30
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2040-03-30
AI Technical Summary
The solid electrolyte used in existing lithium batteries is not ion transport efficiency in the electrode body, resulting in limited battery performance.
A sulfide solid electrolyte containing Li elements, P elements and S elements is used, and tetrahydrofuran is added during its synthesis process. By adjusting the firing conditions, an electrolyte with a high BET specific surface area is obtained, thereby forming an efficient electrode body.
The ion transport efficiency in the electrode body is improved, the ion bending rate is reduced, and the overall performance of the battery is improved.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a sulfide solid electrolyte capable of obtaining an electrode body with good ion transport efficiency. Background Art
[0002] In recent years, with the rapid popularization of information-related devices and communication devices such as personal computers, cameras and mobile phones, the development of batteries used as their power sources has received attention. In addition, in the automotive industry, the development of high-output and high-capacity batteries for electric vehicles or hybrid vehicles has been continuously promoted. At present, lithium batteries have attracted much attention among various batteries from the perspective of high energy density.
[0003] The lithium batteries currently on the market use electrolytes containing flammable organic solvents, so it is necessary to install safety devices to suppress the temperature rise during short circuits and structures to prevent short circuits. In response to this, lithium batteries that replace electrolytes with solid electrolyte layers and make the batteries fully solid do not use flammable organic solvents in the batteries, thereby simplifying safety devices.
[0004] As solid electrolytes used in lithium solid batteries, sulfide solid electrolytes are known. For example, Patent Document 1 discloses a sulfide solid electrolyte, which is produced by dissolving a precursor generated by mechanical milling in N-methylformamide and then drying it. In addition, Patent Document 2 discloses a sulfide solid electrolyte, which is produced by mixing Li2S and P2S5 in dimethoxyethane and then drying it. In addition, Patent Document 3 discloses a method for producing a sulfide solid electrolyte, which dries a slurry containing lithium sulfide in a low temperature environment and a vacuum state and then crystallizes it at a high temperature.
[0005] Prior art literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-191899
[0007] Patent Document 2: Japanese Patent Application Publication No. 2015-232965
[0008] Patent Document 3: Japanese Patent Application Publication No. 2018-080100 Summary of the invention
[0009] The electrode bodies (positive electrode active material layer and negative electrode active material layer) used in all-solid batteries are required to have good ion transport efficiency. The present disclosure has been made in view of the above situation, and its main purpose is to provide a sulfide solid electrolyte that can provide an electrode body with good ion transport efficiency.
[0010] In the present disclosure, a sulfide solid electrolyte is provided, which contains Li element, P element and S element, and contains tetrahydrofuran, and has a BET specific surface area of 8.3 m 2 / g or above.
[0011] According to the present disclosure, a sulfide solid electrolyte having a predetermined BET specific surface area can be formed to obtain an electrode body with good ion transport efficiency. In addition, the sulfide solid electrolyte contains tetrahydrofuran. When synthesizing the sulfide solid electrolyte, tetrahydrofuran is used and synthesized under predetermined conditions, thereby obtaining a sulfide solid electrolyte with a high BET specific surface area.
[0012] In the above disclosure, the above BET specific surface area can be 13.1 m 2 / g or above.
[0013] In the above disclosure, the Raman spectra obtained from PS4 3- The intensity of peak a from tetrahydrofuran is set to Ia, and the intensity of peak b from tetrahydrofuran is set to Ib. In this case, the ratio of the above Ib to the above Ia (Ib / Ia) can satisfy 0.0055≤Ib / Ia<0.266.
[0014] In the above disclosure, the above sulfide solid electrolyte may be amorphous.
[0015] In the above disclosure, the above sulfide solid electrolyte may be crystalline.
[0016] In addition, the present disclosure provides a method for producing a sulfide solid electrolyte, which is a method for producing the above-mentioned sulfide solid electrolyte, comprising: a precursor preparation step of mixing a raw material composition containing constituent components of the above-mentioned sulfide solid electrolyte with tetrahydrofuran to obtain a precursor; and a first calcination step of volatilizing the above-mentioned tetrahydrofuran contained in the above-mentioned precursor.
[0017] According to the present disclosure, since the first calcination step is provided, it is possible to produce a sulfide solid electrolyte containing tetrahydrofuran and having a predetermined BET specific surface area.
[0018] In the above disclosure, the calcination temperature in the first calcination step may be a temperature lower than a crystallization temperature of the sulfide solid electrolyte, and the sulfide solid electrolyte may be amorphous.
[0019] In the above disclosure, the firing temperature in the first firing step may be 100° C. or lower.
[0020] In the above disclosure, the manufacturing method may further include, after the first sintering step, a second sintering step for improving the crystallinity of the sulfide solid electrolyte, the sintering temperature in the second sintering step is a temperature higher than the crystallization temperature of the sulfide solid electrolyte, and the sulfide solid electrolyte is crystalline.
[0021] In the above disclosure, the firing temperature in the second firing step may be 140° C. or higher.
[0022] In addition, the present disclosure provides an electrode body for an all-solid-state battery, comprising an active material and a sulfide solid electrolyte, and further comprising tetrahydrofuran, wherein the volume ratio of the sulfide solid electrolyte in the electrode body is ε, and the ion conductivity of the sulfide solid electrolyte is σ. SE , and the ionic conductivity of the electrode body is set as σ ele In this case, ε×σ SE / σ ele The calculated ion bending ratio was 4.5 or less.
[0023] According to the present disclosure, since the ion bending rate is low, an electrode body with good ion transport efficiency can be formed.
[0024] In addition, in the present disclosure, a fully solid-state battery is provided, comprising a positive electrode active material layer, a negative electrode active material layer, and a solid electrolyte layer formed between the positive electrode active material layer and the negative electrode active material layer, wherein at least one of the positive electrode active material layer and the negative electrode active material layer is the electrode body.
[0025] According to the present disclosure, since the electrode body is provided, an all-solid-state battery having excellent ion transport efficiency can be formed.
[0026] The sulfide solid electrolyte in the present disclosure exerts an effect of being able to obtain an electrode body with excellent ion transport efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a flow chart showing an example of a method for producing a sulfide solid electrolyte in the present disclosure.
[0028] Figure 2 This is a schematic cross-sectional view showing an example of an electrode body in the present disclosure.
[0029] Figure 3 This is a schematic cross-sectional view showing an example of an all-solid-state battery in the present disclosure.
[0030] Figure 4 These are the results of XRD measurement of the sulfide solid electrolytes obtained in Examples 1, 2, 5, and 6 and Comparative Examples 1 and 2.
[0031] Figure 5 These are the results of Raman spectroscopy measurement of the sulfide solid electrolytes obtained in Examples 1 and 2 and Comparative Examples 1 and 2.
[0032] Figure 6 : are SEM images of the sulfide solid electrolytes obtained in Example 1 and Comparative Example 1.
[0033] Figure 7 This is a cross-sectional SEM image of the sulfide solid electrolyte obtained in Example 1.
[0034] Figure 8 It is a graph showing the relationship between the BET specific surface area and the ion bending rate.
[0035] Fig. 9 This is a graph showing the relationship between the sintering temperature (heat treatment temperature) and the BET specific surface area.
[0036] Fig.10 This is a cross-sectional SEM image of the positive electrode shown according to the pressing pressure during powder compaction.
[0037] Description of Reference Numerals
[0038] 1…Active substances
[0039] 2…Sulfide solid electrolyte
[0040] 10…Electrode body
[0041] 11…Positive electrode active material layer
[0042] 12…Negative electrode active material layer
[0043] 13…Solid electrolyte layer
[0044] 14…Positive electrode collector
[0045] 15…Negative electrode collector
[0046] 20…All-solid-state battery DETAILED DESCRIPTION
[0047] Hereinafter, the sulfide solid electrolyte, the method for producing the sulfide solid electrolyte, the electrode body, and the all-solid-state battery in the present disclosure will be described in detail.
[0048] A. Sulfide solid electrolyte
[0049] The sulfide solid electrolyte disclosed in the present invention is a sulfide solid electrolyte containing Li, P and S elements, and contains tetrahydrofuran, and has a BET specific surface area of 8.3 m 2 / g or above.
[0050] According to the present disclosure, a sulfide solid electrolyte having a predetermined BET specific surface area can be formed to obtain an electrode body with good ion transport efficiency. Moreover, the sulfide solid electrolyte contains tetrahydrofuran. By using tetrahydrofuran when synthesizing the sulfide solid electrolyte and synthesizing it under predetermined conditions, a sulfide solid electrolyte with a high BET specific surface area can be obtained. That is, tetrahydrofuran is a residue of the solvent added during manufacture. In addition, the sulfide solid electrolyte in the present disclosure is a porous substance with a large BET specific surface area. It is speculated that if such a sulfide solid electrolyte is used for an electrode body, the pores are destroyed by pressing, thereby the interface contact between the sulfide solid electrolyte and the active material becomes good. In addition, it is speculated that the sulfide solid electrolyte is moistened by tetrahydrofuran, thereby achieving high filling. As a result, it is speculated that the ion curvature in the electrode body can be reduced, and the ion transport efficiency becomes good. Details about the ion curvature are described below.
[0051] Here, Patent Document 2 discloses that tetrahydrofuran can be used as a solvent in the production of a sulfide solid electrolyte. However, Patent Document 2 states that "the residual organic solvent is completely evaporated and removed", and does not describe or suggest the idea that the sulfide solid electrolyte contains a solvent (tetrahydrofuran).
[0052] The sulfide solid electrolyte in the present disclosure contains Li element, P element and S element. In addition, it may contain at least one of O element and halogen element (e.g., F element, Cl element, Br element, I element). The sulfide solid electrolyte preferably contains an ion conductor containing Li element, P element and S element. The ion conductor may further contain O element. In addition, the sulfide solid electrolyte may contain LiX (X is a halogen element) in addition to the ion conductor.
[0053] The ion conductor in the present disclosure preferably contains PS4 3- Structure as the main body. Because of its high Li ion conductivity. PS4 in ion conductor 3- The ratio of the structure to the total anion structure is, for example, 50 mol% or more, 70 mol% or more, or 90 mol% or more. 3- The S element in the structure may be replaced by an O element. In addition, when the sulfide solid electrolyte contains an ion conductor and LiX (X is a halogen element), the ratio of LiX contained in the sulfide solid electrolyte is, for example, 5 mol% or more and 35 mol% or less. In the sulfide solid electrolyte, as the above-mentioned X, one halogen element may be contained, or two or more halogen elements may be contained.
[0054] The sulfide solid electrolyte in the present disclosure may be crystalline or amorphous (amorphous). Furthermore, "amorphous" in the present disclosure means that in the X-ray diffraction (XRD) measurement, no peak of the sulfide solid electrolyte is observed, that is, no periodicity as a crystal is observed, and a so-called halo pattern is observed. On the other hand, "crystalline" means that in the XRD measurement, a peak of the sulfide solid electrolyte is observed. The crystallization temperature of the sulfide solid electrolyte is, for example, above 120°C and below 200°C. Furthermore, the crystallization temperature (T c ) can be obtained by differential thermal analysis (DTA).
[0055] In addition, the shape of the sulfide solid electrolyte may be, for example, a prism shape. The average particle size (D 50 ) is, for example, 0.1 μm or more, 0.5 μm or more, 1 μm or more, or 5 μm or more. On the other hand, the average particle size (D 50 ) is, for example, 50 μm or less, 20 μm or less, or 10 μm or less. The average particle size (D 50 ) can be obtained from the results of particle size distribution measurement using, for example, a laser diffraction scattering method. In addition, it is preferred that the ion conductivity is high. The ion conductivity at 25°C is, for example, 1×10 -4 S / cm or more, can be 1×10 -3 S / cm or more.
[0056] The BET specific surface area of the sulfide solid electrolyte is 8.3 m 2 / g or more, can be 13.1m 2 / g or more, can also be 27.5m 2 / g or more. On the other hand, the BET specific surface area of the sulfide solid electrolyte is, for example, 50 m 2 / g or less, can be 40m 2 / g or less, can be 37.1m 2 / g or less, and can also be 28.7m 2 / g or less. The BET specific surface area can be calculated by the BET method using, for example, a pore distribution measuring device. The BET specific surface area can be adjusted by changing the amount of tetrahydrofuran added and the calcination conditions in the method for producing a sulfide solid electrolyte described later.
[0057] The sulfide solid electrolyte in the present disclosure contains tetrahydrofuran. The presence or absence of tetrahydrofuran can be confirmed by, for example, X-ray diffraction (XRD) measurement and Raman spectroscopy measurement. In addition, when the sulfide solid electrolyte has PS4 3-In the case of the structure, the content of tetrahydrofuran can be determined by Raman spectroscopy with the 2850 cm -1 ~3050cm -1 The intensity of peak b Ib relative to that from PS4 3- Structure 410cm -1 It is obtained by calculating the ratio (Ib / Ia) of the intensity Ia of the peak a near the peak a. In the sulfide solid electrolyte disclosed in the present invention, Ib / Ia is, for example, greater than 0.0055, may be greater than 0.043, or may be greater than 0.1. On the other hand, Ib / Ia is, for example, less than 0.266, may be less than 0.2, or may be less than 0.15. If the amount of tetrahydrofuran is too small, the expected BET specific surface area may not be obtained. On the other hand, if the amount of tetrahydrofuran is too much, the sulfide solid electrolyte may agglomerate. The amount of tetrahydrofuran can be adjusted by changing the sintering conditions in the method for manufacturing the sulfide solid electrolyte described later.
[0058] B. Method for producing sulfide solid electrolyte
[0059] Figure 1 This is a flow chart showing an example of a method for producing a sulfide solid electrolyte in the present disclosure.
[0060] The method for producing a sulfide solid electrolyte disclosed in the present invention comprises: a precursor preparation step of mixing a raw material composition containing constituent components of a sulfide solid electrolyte with tetrahydrofuran to obtain a precursor; and a first calcination step of volatilizing the tetrahydrofuran contained in the precursor. In addition, if necessary, a second calcination step of improving the crystallinity of the sulfide solid electrolyte may be further included after the first calcination step.
[0061] According to the present disclosure, since the first calcination step is provided, it is possible to produce a sulfide solid electrolyte containing tetrahydrofuran and having a predetermined BET specific surface area.
[0062] 1. Precursor preparation process
[0063] The precursor preparation step in the present disclosure is a step of mixing a raw material composition containing the constituent components of the above-mentioned sulfide solid electrolyte with tetrahydrofuran to obtain a precursor.
[0064] The raw material composition may contain Li, P and S as constituent components, and may also contain O and halogen elements (such as F, Cl, Br, I). Examples of compounds containing the Li element include Li sulfides and Li oxides. Specifically, Li2S can be cited as Li sulfides. Specifically, Li oxides can be cited as Li2O. In addition, examples of compounds containing the P element include simple P, P oxides, P sulfides, etc. Specifically, P sulfides can be cited as P2S5. Specifically, P oxides can be cited as P2O5. The compound containing the S element is not particularly limited, and may be a simple substance or a sulfide. Examples of sulfides include sulfides containing the above elements. The raw material composition can be prepared by mixing these compounds in any proportion. When the raw material composition contains Li2S and P2S5, the ratio of Li2S to the total of Li2S and P2S5 is, for example, 70 mol% or more, 72 mol% or more, or 74 mol% or more. On the other hand, the ratio of Li2S to the total of Li2S and P2S5 is, for example, 80 mol% or less, 78 mol% or less, or 76 mol% or less.
[0065] Tetrahydrofuran is not particularly limited, and commercial products can be used, for example. The amount of tetrahydrofuran added is, for example, 20 times or more, or 30 times or more, relative to the raw material composition by weight ratio. On the other hand, the amount of tetrahydrofuran is, for example, 50 times or less, or 40 times or less, relative to the raw material composition by weight ratio.
[0066] The method for mixing the raw material composition and tetrahydrofuran is not particularly limited, and for example, a method of stirring in a glass container such as a beaker using a stirrer or the like can be cited. The stirring temperature is not particularly limited, and is, for example, above 25°C, above 30°C, or above 35°C. On the other hand, the stirring temperature is, for example, below 50°C, or below 40°C. In addition, the stirring time is not particularly limited, and is, for example, above 48 hours, above 60 hours, or above 72 hours. On the other hand, the stirring time can be, for example, below 120 hours, below 108 hours, below 96 hours, or below 84 hours.
[0067] 2. First sintering process
[0068] The first calcining step is a step of volatilizing tetrahydrofuran contained in the precursor.
[0069] In the first calcination step, tetrahydrofuran is volatilized from the precursor by calcination. The calcination temperature in the first calcination step is not particularly limited as long as it is a temperature at which tetrahydrofuran can be volatilized. The calcination temperature may be, for example, lower than the crystallization temperature (T c ), or the crystallization temperature of the sulfide solid electrolyte (T c In the former case, an amorphous sulfide solid electrolyte can be obtained, and in the latter case, a crystalline sulfide solid electrolyte can be obtained.
[0070] In the first sintering step, when the temperature is lower than the crystallization temperature (T c ) temperature, the firing temperature is, for example, (T c -10℃) or less, or (T c On the other hand, in the first sintering step, when the crystallization temperature (T c ) or above, the sintering temperature may be, for example, T c , can also be greater than T c In the latter case, the calcination temperature is, for example, (T c +10℃) and above (T c The specific firing temperature of the first firing step is, for example, 300°C or less, 200°C or less, 140°C or less, 120°C or less, or 100°C or less. On the other hand, the firing temperature in the first firing step is, for example, 60°C or more, 70°C or more, or 80°C or more.
[0071] The firing time in the first firing step is, for example, 1 hour or more, 12 hours or more, or 24 hours or more. On the other hand, the firing time in the first firing step is, for example, 60 hours or less, 48 hours or less, or 36 hours or less.
[0072] The calcination in the first calcination step is preferably carried out in an open system. An open system refers to a system in which tetrahydrofuran can be irreversibly volatilized from a precursor. For example, an atmospheric pressure open system and a reduced pressure open system can be cited. As a reduced pressure open system, for example, vacuuming can be cited.
[0073] Before the first calcination step, a drying treatment may be performed to dry the precursor. The drying temperature is, for example, 10° C. to 60° C. The drying atmosphere may be, for example, an inert gas atmosphere such as argon.
[0074] 3. Second sintering process
[0075] In the present disclosure, after the first calcination step, a second calcination step for improving the crystallinity of the sulfide solid electrolyte may be performed, thereby obtaining a crystalline sulfide solid electrolyte.
[0076] The calcination temperature in the second calcination step is the crystallization temperature (T c The firing temperature in the second firing step may be, for example, T c , can also be greater than T c In the latter case, the calcination temperature is, for example, (T c +10℃) and above (T c The specific firing temperature of the second firing step is, for example, 140°C or more, or 180°C or more. On the other hand, the firing temperature of the second firing step is, for example, 300°C or less, or 200°C or less. The firing temperature of the first firing step and the firing temperature of the second firing step may be the same temperature or different temperatures. In the latter case, the temperature difference is, for example, 10°C or more.
[0077] The firing time of the second firing process is, for example, more than 6 hours, or more than 8 hours. On the other hand, the firing time of the second firing process is less than 12 hours, or less than 10 hours. The firing in the second firing process is preferably carried out under a closed system. In addition, the firing in the second firing process is preferably carried out under a reduced pressure atmosphere.
[0078] 4. Sulfide solid electrolyte
[0079] The sulfide solid electrolyte obtained through the above-mentioned steps is the same as that described in the above-mentioned "A. Sulfide solid electrolyte", and thus the description thereof is omitted here.
[0080] C. Electrode body
[0081] Figure 2 This is a schematic cross-sectional view showing an example of an electrode body in the present disclosure. Figure 2 The electrode body 10 shown is used for an all-solid-state battery and contains an active material 1 and a sulfide solid electrolyte 2. In addition, the electrode body 10 further contains tetrahydrofuran (not shown). In addition, when the volume ratio of the sulfide solid electrolyte 2 in the electrode body 10 is ε and the ion conductivity of the sulfide solid electrolyte 2 is σ SE , and the ionic conductivity of the electrode body 10 is σ ele In the case of SE / σ ele The calculated ion bending ratio was 4.5 or less.
[0082] According to the present disclosure, since the ion bending rate is low, an electrode body with good ion transport efficiency can be formed. In addition, the sulfide solid electrolyte contained in the electrode body usually contains tetrahydrofuran. When synthesizing the sulfide solid electrolyte, tetrahydrofuran is used, and the sulfide solid electrolyte with a high BET specific surface area can be obtained by synthesizing under predetermined conditions. By using such a sulfide solid electrolyte, an electrode body with good ion transport efficiency can be formed.
[0083] The ion curvature in the present disclosure is 4.5 or less, and may be 4.0 or less, or 3.5 or less. The ion curvature is an index defined as follows. Here, the ion conduction of the electrode body slows down correspondingly to the curvature of the ions in the electrode body relative to the inherent ion conduction of the solid electrolyte. Therefore, the effective ion conductivity K of the electrode body is eff It can be expressed by the following formula.
[0084] K eff =ε×K / τ
[0085] Here, ε is the volume ratio of the sulfide solid electrolyte in the electrode body, K is the ion conductivity of the sulfide solid electrolyte, and τ is the ion bending rate. Therefore, the ion bending rate τ can be expressed by the following formula.
[0086] τ=ε×K / K eff
[0087] That is, the smaller τ is, the more effective ionic conductivity K of the electrode body is. eff The higher the K, the higher the ionic conductivity of the sulfide solid electrolyte. SE Come and get it. eff The ionic conductivity of the electrode body can be measured by ele Come and ask for it.
[0088] The electrode body in the present disclosure contains an active material and a sulfide solid electrolyte. The electrode body may further contain at least one of a conductive material and a binder. The sulfide solid electrolyte contained in the electrode body is preferably obtained by compressing the sulfide solid electrolyte described in the above "A. Sulfide solid electrolyte".
[0089] The active material can be a positive electrode active material or a negative electrode active material. Examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and other rock salt layer active materials, lithium manganate (LiMn2O4), Li(Ni 0.5 Mn 1.5 )O4 and other spinel active materials, lithium titanate (Li4Ti5O 12), LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4 and other olivine-type active materials. The shape of the positive electrode active material can be formed into, for example, a particle shape or a thin film shape. When the positive electrode active material is in the form of particles, the positive electrode active material can be a primary particle or a secondary particle. In addition, the average particle size (D 50 ) is preferably, for example, not less than 1 nm and not more than 100 μm, and more preferably not less than 10 nm and not more than 30 μm.
[0090] On the other hand, examples of negative electrode active materials include metal active materials and carbon active materials. Examples of metal active materials include In, Al, Si, Sn, etc. On the other hand, examples of carbon active materials include mesocarbon microbeads (MCMB), highly oriented pyrolytic graphite (HOPG), hard carbon, and soft carbon. In addition, examples of lithium titanate (Li4Ti5O 12 ) and other metal oxides. The shape of the negative electrode active material can be formed into, for example, a particle shape, a thin film shape, etc. When the negative electrode active material is in the form of particles, the negative electrode active material can be a primary particle or a secondary particle. In addition, the average particle size (D 50 ) is preferably, for example, not less than 1 nm and not more than 100 μm, and more preferably not less than 10 nm and not more than 30 μm.
[0091] In addition, the electrode body in the present disclosure may contain a conductive material and a binder as needed. As the conductive material, a carbon material may be cited. As the binder, a fluorine-based binder such as polyvinylidene fluoride (PVdF) and a rubber-based binder such as butyl rubber (BR) may be cited.
[0092] The thickness of the electrode body is not particularly limited, and is, for example, 0.1 μm or more and 1000 μm or less.
[0093] The manufacturing method of the electrode body in the present disclosure is not particularly limited. As the manufacturing method of the electrode body, for example, the following method can be cited, which comprises: a preparation step of preparing an electrode mixture by mixing the sulfide solid electrolyte described in the above "A. Sulfide solid electrolyte", an active material, and a dispersion medium, and then drying; and a pressing step of pressing the above electrode mixture.
[0094] The sulfide solid electrolyte and the active material are as described above. In addition, as the dispersion medium, an organic solvent such as heptane can be cited. Mixing and drying are not particularly limited, and can be carried out by conventionally known methods. The pressing step is also not particularly limited, and for example, a method of uniaxial pressing at a pressure of 100 MPa or more and 600 MPa or less can be cited.
[0095] D. All-solid-state battery
[0096] Figure 3 This is a schematic cross-sectional view showing an example of an all-solid-state battery in the present disclosure. Figure 3 The all-solid-state battery 20 shown has: a positive electrode active material layer 11, a negative electrode active material layer 12, a solid electrolyte layer 13 formed between the positive electrode active material layer 11 and the negative electrode active material layer 12, a positive electrode collector 14 for collecting current from the positive electrode active material layer 11, and a negative electrode collector 15 for collecting current from the negative electrode active material layer 14. Moreover, at least one of the positive electrode active material layer 11 and the negative electrode active material layer 12 is the above-mentioned electrode body.
[0097] According to the present disclosure, by using the above-mentioned electrode body, an all-solid-state battery with excellent ion transport efficiency can be formed.
[0098] 1. Positive electrode active material layer and negative electrode active material layer
[0099] At least one of the positive electrode active material layer and the negative electrode active material layer is the electrode body described in the above "B. Electrode body". Only the positive electrode active material layer may be the above electrode body, or only the negative electrode active material layer may be the above electrode body. In addition, both the positive electrode active material layer and the negative electrode active material layer may be the above electrode body.
[0100] 2. Positive electrode collector and negative electrode collector
[0101] The positive electrode collector and the negative electrode collector have the function of collecting electrons of the positive electrode active material layer and the negative electrode active material layer, respectively. The positive electrode collector and the negative electrode collector are not particularly limited, and the previously known positive electrode collector and negative electrode collector used in all-solid-state batteries can be formed. As the positive electrode collector, for example, Al and SUS can be mentioned. As the negative electrode collector, for example, Cu and Ni can be mentioned. Furthermore, the thickness and shape of the positive electrode collector and the negative electrode collector can be appropriately selected according to the purpose of the battery.
[0102] 3. Solid electrolyte layer
[0103] The solid electrolyte layer is a layer formed between the positive electrode active material layer and the negative electrode active material layer. The solid electrolyte layer contains at least a solid electrolyte and may further contain a binder as necessary.
[0104] The solid electrolyte is not particularly limited, and any conventionally known solid electrolyte used in all-solid batteries can be used, and is preferably the same as the sulfide solid electrolyte contained in the electrode body. The binder is the same as described in "B. Electrode Body" above.
[0105] The thickness of the solid electrolyte layer is not particularly limited, and is, for example, 0.1 μm or more and 1000 μm or less.
[0106] 4. All-solid-state batteries
[0107] The all-solid battery in the present disclosure is preferably an all-solid lithium ion battery. In addition, the all-solid battery in the present disclosure may be a primary battery or a secondary battery, but the latter is preferred. Because it can be repeatedly charged and discharged, it is useful as, for example, a vehicle-mounted battery. Furthermore, the secondary battery also includes the use of a secondary battery as a primary battery (the use for the purpose of only one discharge after charging). As the shape of the all-solid battery, for example, a coin type, a laminated type, a cylindrical type, and a square type can be cited. In addition, the all-solid battery may have only one power generation element, or may have more than two power generation elements. In the latter case, a plurality of power generation elements may be connected in parallel or in series.
[0108] The present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and all those having substantially the same structure and having the same function and effect as the technical concept described in the scope of the claims in the present disclosure are included in the technical scope of the present disclosure.
[0109] Example
[0110] [Example 1]
[0111] (Preparation of sulfide solid electrolyte)
[0112] Li2S and P2S5 were weighed at a molar ratio of Li2S:P2S5=75:25 to obtain a raw material composition. The raw material composition and tetrahydrofuran, which was 20 times the weight ratio of the raw material composition, were placed in a glass container, stirred at 25°C for 72 hours, and the precipitated powder was recovered as a precursor of a sulfide solid electrolyte. The recovered precursor was dried at 25°C under an argon atmosphere, and then calcined at 100°C for 1 hour under atmospheric pressure (open system) (first calcination). The obtained calcined body was vacuum-sealed in a quartz tube, and the quartz tube was calcined at 140°C for 12 hours in a muffle furnace (second calcination) to produce a sulfide solid electrolyte.
[0113] (Preparation of positive electrode mixture)
[0114] The oxide active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), the sulfide solid electrolyte and the conductive material (VGCF) were added into heptane, stirred with an ultrasonic homogenizer, and then dried to prepare a positive electrode mixture. Furthermore, the volume ratio of the oxide active material to the sulfide solid electrolyte was set to oxide active material: sulfide solid electrolyte = 40:60, and the conductive material was set to 2 volume%.
[0115] (Production of positive electrode)
[0116] 100 mg of the positive electrode mixture was put into a cylinder with a diameter of 11.28 mm, and pelletized by applying a pressure of 600 MPa using a uniaxial press to produce a positive electrode.
[0117] [Example 2]
[0118] The first calcination was performed in the same manner as in Example 1. The calcined body obtained in the first calcination was evacuated at 140° C. for 12 hours using a sample dryer (second calcination) to produce a sulfide solid electrolyte. A sulfide solid electrolyte and a positive electrode were produced in the same manner as in Example 1 except that the obtained sulfide solid electrolyte was used.
[0119] [Example 3]
[0120] A sulfide solid electrolyte and a positive electrode were produced in the same manner as in Example 1 except that the calcination temperature in the first calcination was set to 80° C., the calcination time was changed to 2 hours, and the second calcination was not performed.
[0121] [Example 4]
[0122] A sulfide solid electrolyte and a positive electrode were produced in the same manner as in Example 1 except that the firing temperature in the second firing was changed to 300°C.
[0123] [Example 5]
[0124] A sulfide solid electrolyte and a positive electrode were produced in the same manner as in Example 1 except that the first calcination was performed at 80° C. for 48 hours while evacuating the vacuum, and the second calcination was not performed.
[0125] [Example 6]
[0126] A sulfide solid electrolyte and a positive electrode were produced in the same manner as in Example 1 except that the first calcination was performed at 80° C. for 12 hours under atmospheric pressure (open system) and the second calcination was not performed.
[0127] [Comparative Example 1]
[0128] Li2S and P2S5 were weighed at a molar ratio of Li2S:P2S5=75:25 to obtain a mixed powder. The obtained mixed powder was mechanically milled using a planetary ball mill at 600 rpm for 24 hours. Thereafter, the mixture was calcined at 550°C in an argon atmosphere to produce a sulfide solid electrolyte. A sulfide solid electrolyte and a positive electrode were produced in the same manner as in Example 1 except that the obtained sulfide solid electrolyte was used.
[0129] [Comparative Example 2]
[0130] A sulfide solid electrolyte and a positive electrode were produced in the same manner as in Example 2, except that the first calcination was not performed and vacuum evacuation was not performed in the second calcination.
[0131] [evaluate]
[0132] (X-ray diffraction measurement)
[0133] The sulfide solid electrolytes obtained in Examples 1 to 6 and Comparative Examples 1 and 2 were subjected to X-ray diffraction (XRD) measurement using CuKα radiation. Representative results are shown in FIG. Figure 4 .like Figure 4 As shown, in Examples 1, 2 and Comparative Example 1, the peak of β-Li3PS4 can be confirmed, confirming that it is crystalline. On the other hand, in Comparative Example 2, the peak of β-Li3PS4 cannot be confirmed. It is believed that the first calcination was not carried out, and only the second calcination without vacuuming was carried out, so it is a peak shape in a state where a large amount of tetrahydrofuran remains. In addition, in Examples 5 and 6, a halo peak was confirmed, confirming that the sulfide solid electrolyte is amorphous. In addition, although not shown in the figure, Example 3 was also confirmed to be amorphous in the same way as Examples 5 and 6.
[0134] (Raman spectroscopy)
[0135] Raman spectroscopy was performed on the sulfide solid electrolytes obtained in Examples 1 to 6 and Comparative Examples 1 and 2. Representative results are shown in FIG. Figure 5 .like Figure 5 As shown, in Examples 1, 2 and Comparative Example 2, the 2850 cm -1 ~3050cm -1 The peak derived from tetrahydrofuran. In particular, a large amount of tetrahydrofuran was confirmed in Comparative Example 2. In addition, the peak at 410 cm -1 Nearby from PS4 3- The intensity of peak a at Ia and 2850 cm -1 ~3050cm -1 The intensity Ib of the peak b derived from tetrahydrofuran was calculated to obtain Ib / Ia. The results are shown in Table 1.
[0136] (SEM observation)
[0137] The sulfide solid electrolytes obtained in Examples 1 to 6 and Comparative Examples 1 and 2 were observed using a SEM (scanning electron microscope). Figure 6 As shown in (a), it was confirmed that the sulfide solid electrolyte obtained in Example 1 had a prism structure with a size of about 5 μm to 20 μm. Figure 6 As shown in (b), it was confirmed that the sulfide solid electrolyte obtained in Comparative Example 1 did not have a prismatic shape, unlike Example 1.
[0138] In addition, the sulfide solid electrolyte obtained in Example 1 was cut by sealing with resin and the cross section was observed. The results are shown in FIG. Figure 7 .like Figure 7 As shown, it was confirmed that the sulfide solid electrolyte obtained in Example 1 had a porous structure. It is presumed that such a porous structure was formed when THF volatilized during the preparation of the sulfide solid electrolyte.
[0139] (Determination of BET specific surface area)
[0140] The BET specific surface area was measured for the sulfide solid electrolytes obtained in Examples 1 to 6 and Comparative Examples 1 and 2. Specifically, the BET specific surface area was calculated and confirmed using a pore distribution measuring apparatus according to the BET method. The results are shown in Table 1.
[0141] (Determination of filling rate)
[0142] For the sulfide solid electrolytes obtained in Examples 1 to 2, 4 and Comparative Example 1, the filling rate during pressing was measured. Specifically, after 100 mg of the sulfide solid electrolyte was uniaxially pressed at a pressure of 600 MPa to form pellets, the height of the pellets was measured and the volume was calculated. Then, the filling rate during pressing was obtained by dividing the volume obtained from the true density by the calculated volume. The results are shown in Table 1.
[0143] (Determination of ion bending rate)
[0144] The ion bending rate was measured for the positive electrodes obtained in Examples 1 to 6 and Comparative Examples 1 and 2. First, the conductivity σ of the solid electrolyte was determined. SE Specifically, the impedance measurement was performed on pellets obtained by uniaxially pressing 100 mg of the produced sulfide solid electrolyte at 600 MPa. σ was calculated from the resistance value of the semicircle of the obtained Nyquist line diagram and the thickness of the pellet. SE .
[0145] Next, the conductivity σ of the electrode body is calculated ele Specifically, the positive electrode was sandwiched between the upper and lower parts of the prepared positive electrode by a sulfide solid electrolyte, and then sandwiched between the upper and lower parts by a Li foil to form a sample. The impedance of the sample was measured. σ was calculated based on the resistance value of the semicircle of the obtained Nyquist line diagram and the thickness of the positive electrode. ele The volume ratio ε of the sulfide solid electrolyte was determined from the volume ratio of the sulfide solid electrolyte used in each example and each comparative example. SE and σ ele The ion bending rate (τ) is calculated by the following formula. The results are shown in Figure 8 and Table 1.
[0146] Ion bending rate (τ) = ε × σSE / σ ele
[0147] Table 1
[0148]
[0149] like Figure 8 As shown in Table 1, it contains tetrahydrofuran and has a BET specific surface area of 8.3 m 2 In Examples 1 to 6 with a surface area of 1.5 m / g or more, the ion bending ratio was 4.5 or less. On the other hand, in Comparative Examples 1 and 2, the ion bending ratio was 8.8 or more. In particular, it was confirmed that the BET specific surface area was 8.3 m 2 / g or more, the ion bending rate drops sharply. In addition, as for the filling rate, Examples 1, 2, and 4 are higher than Comparative Example 1. It is considered that the sulfide solid electrolyte obtained in each Example has a porous structure, so the filling rate becomes high. In addition, it can be said that the sulfide solid electrolyte obtained in each Example contains a small amount of THF, so it is in a wet state. Therefore, the filling rate may also become high.
[0150] [Reference Examples 1 to 7]
[0151] The relationship between the calcination temperature (heat treatment temperature) in the first calcination and the BET specific surface area of the obtained sulfide solid electrolyte was investigated. The results are shown in Fig. 9 and Table 2. Furthermore, Fig. 9 Reference Examples 3 and 5 in Table 2 correspond to the above-mentioned Examples 3 and 1, respectively.
[0152] Table 2
[0153]
[0154] like Fig. 9 As shown in Table 2, it was confirmed that the BET specific surface area is affected if the calcination temperature (heat treatment temperature) is changed. In particular, it was confirmed that the BET specific surface area becomes the largest at 80°C, and if the temperature is higher than 80°C, there is a tendency for the BET specific surface area to decrease. It is speculated that this is because tetrahydrofuran evaporates all at once near 80°C, thereby causing porosity and increasing the BET specific surface area. In addition, it is speculated that when the temperature is higher than 80°C, the porous structure is sintered and destroyed, so the BET specific surface area decreases. In this way, even if the calcination temperature is simply increased, the increase in the BET specific surface area is not confirmed.
[0155] [Reference Example 8]
[0156] The positive electrodes were prepared in the same manner as in Example 1 except that the pressing pressure during powder compaction was changed to 100 MPa, 200 MPa, and 400 MPa, and cross-sectional SEM images of the positive electrodes were obtained. Fig.10 .
[0157] like Fig.10 As shown in the figure, when the pressing pressure is 200 MPa, the sulfide solid electrolyte is broken into particles of 100 nm to 200 nm, thereby confirming that it is filled more highly than when it is 100 MPa. Moreover, at a pressing pressure of 600 MPa, it is filled with almost no gaps. In this way, it is speculated that in the electrode body disclosed in the present invention, a sulfide solid electrolyte with a small particle size is not used from the beginning, and the sulfide solid electrolyte is micronized by the pressing pressure, thereby achieving high filling.
Claims
1. A method for producing a sulfide solid electrolyte, wherein the sulfide solid electrolyte contains Li, P and S elements and tetrahydrofuran, and the BET specific surface area of the sulfide solid electrolyte is 8.3 m 2 / g or more, the method for producing a sulfide solid electrolyte comprises a precursor preparation step, a first sintering step, and a second sintering step after the first sintering step, In the precursor preparation step, a raw material composition containing constituent components of the sulfide solid electrolyte and the tetrahydrofuran are mixed to obtain a precursor. In the first calcining step, the tetrahydrofuran contained in the precursor is volatilized. In the second calcining step, the crystallinity of the sulfide solid electrolyte is improved. The first sintering step is performed in an open system, and the second sintering step is performed in a reduced pressure atmosphere. The sulfide solid electrolyte obtained by Raman spectroscopy from PS4 3- The intensity of the peak a derived from tetrahydrofuran is defined as Ia, and the intensity of the peak b derived from tetrahydrofuran is defined as Ib. In this case, a ratio of Ib to Ia (Ib / Ia) satisfies 0.0055≤Ib / Ia<0.
266. 2 . The method for producing a sulfide solid electrolyte according to claim 1 , wherein Ib / Ia satisfies 0.0055≤Ib / Ia≤0.
135.
3. The method for producing a sulfide solid electrolyte according to claim 1, The calcination temperature in the first calcination step is 100° C. or lower.
4. The method for producing a sulfide solid electrolyte according to claim 1, The firing temperature in the second firing step is a temperature equal to or higher than the crystallization temperature of the sulfide solid electrolyte. The sulfide solid electrolyte is crystalline.
5. The method for producing a sulfide solid electrolyte according to claim 4, The firing temperature in the second firing step is 140° C. or higher. 6 . The method for producing a sulfide solid electrolyte according to claim 1 , comprising a drying process of drying the precursor before the first calcining step. 7 . The method for producing a sulfide solid electrolyte according to claim 1 , wherein a sintering time in the first sintering step is 1 hour to 60 hours. 8 . The method for producing a sulfide solid electrolyte according to claim 1 , wherein a sintering time in the second sintering step is 6 hours to 12 hours.
Citation Information
Patent Citations
Liquid solution for formation of a solid electrolyte-containing layer of all-solid type lithium secondary battery, all-solid type lithium secondary battery, and method for manufacturing the same
JP2014191899A
Sulfide solid electrolyte, and method of producing sulfide solid electrolyte
JP2015232965A
Production method for sulfide-based solid electrolyte by wet process
JP2018080100A